Tetanus-diphtheria vaccine can prime SARS-CoV-2 cross-reactive T cells - Fernandez, Sara Alonso; Pelaez-Prestel, Hector F.; Fiyouzi, Tara; Gomez-Perosanz, Marta; Reiné, Jesús; Reche, Pedro A. (Frontiers in Immunology, 2024)
Vaccines containing tetanus-diphtheria antigens have been postulated to induce cross-reactive immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which could protect against coronavirus disease . In this work, we investigated the capacity of Tetanusdiphtheria (Td) vaccine to prime existing T cell immunity to SARS-CoV-2. To that end, we first collected known SARS-CoV-2 specific CD8 + T cell epitopes targeted during the course of SARS-CoV-2 infection in humans and identified as potentially cross-reactive with Td vaccine those sharing similarity with tetanus-diphtheria vaccine antigens, as judged by Levenshtein edit distances (≤ 20% edits per epitope sequence). As a result, we selected 25 potentially cross-reactive SARS-CoV-2 specific CD8 T cell epitopes with high population coverage that were assembled into a synthetic peptide pool (TDX pool). Using peripheral mononuclear cells, we first determined by intracellular IFNg staining assays existing CD8 + T cell recall responses to the TDX pool and to other peptide pools, including overlapping peptide pools covering SARS-CoV-2 Spike protein and Nucleocapsid phosphoprotein (NP). In the studied subjects, CD8 + T cell recall responses to Spike and TDX peptide pools were dominant and comparable, while recall responses to NP peptide pool were less frequent and weaker. Subsequently, we studied responses to the same peptides using antigen-inexperienced naive T cells primed/stimulated in vitro with Td vaccine. Priming stimulations were carried out by coculturing naive T cells with autologous irradiated peripheral mononuclear cells in the presence of Td vaccine, IL-2, IL-7 and IL-15. Interestingly, naive CD8 T cells stimulated/primed with Td vaccine responded strongly and specifically to the TDX pool, not to other SARS-CoV-2 peptide pools.Finally, we show that Td-immunization of C57BL/6J mice elicited T cells cross-reactive with the TDX pool. Collectively, our findings support that tetanus-diphtheria vaccines can prime SARS-CoV-2 cross-reactive T cells and likely contribute to shape the T cell responses to the virus.